Linking earned income, psychological capital and social grant dependency: Empirical evidence from rural KwaZulu-Natal (South Africa) and implications for policy - U. Chipfupa; E. Wale (Journal of Economic Structures, 2020)
Understanding the motivation that smallholders have for working and earning their livelihood is critical in enhancing the effectiveness of agricultural policies. This is especially important in a country like South Africa where social grant is an important source of unearned income. The study sought to find out what affects smallholders' motivation to work by assessing the relationship between earned income, psychological capital and social grant dependency. We use data from 458 smallholders in four irrigation communities in rural KwaZulu-Natal and employ a complementary loglog fractional response model to analyse the data. The study revealed that endowment with positive psychological capital, gender, membership to an irrigation scheme and land owner-ship positively affect smallholders' propensity to earn their livelihoods from farm and non-farm income. Social grant support and dependency ratio negatively affect the same. The findings support the thesis that, if not properly managed, social transfers can have a negative impact on smallholders' motivation to work and earn their livelihoods, resulting in a dependency syndrome. Depending on the context, spatial differences can either positively or negatively affect farmers' motivation to work. In conclusion, limited focus on the human and social capital development and hence psychological capital affect smallholders' propensity to work. Small-scale irrigation schemes remain a viable option for increasing employment and incomes in the sector, whilst social and cultural norms continue to reduce women's ability to engage in economic activities. The paper recommends the need to recognise the critical importance of psychological capital (mindset), streamline and improve targeting of social grant support, promote smallholder irrigation and invest in the infrastructure that enhances participation of women in economic activities.
Keywords: 330; Unearned income; Motivation to work; Psychological capital; Social grant; Rural livelihoods